Association between early childhood caries and anthropometric growth and nutritional status in preschool children: a cross-sectional study - Cao, Zhenzhen; Yu, Ran; Ma, Jingru; Zhang, Ying; Dong, Xi; Fan, Lixin (Frontiers in Pediatrics, 2025)
ObjectiveTo estimate the prevalence and dmft burden of early childhood caries (ECC) among preschool children and to examine associations between ECC and anthropometric growth indicators (HAZ, WAZ, WHZ) as well as behavioral and parental factors.MethodsWe conducted a cross-sectional study of 380 children aged 3–6 years selected via multistage cluster sampling from 15 kindergartens in Shijiazhuang, China. ECC was assessed according to WHO Oral Health Survey methods, and dmft (decayed, missing, and filled primary teeth) was calculated. Anthropometric growth was evaluated using WHO Z-scores: height-for-age (HAZ), weight-for-age (WAZ), and weight-for-height (WHZ), with standard cutoffs (Z < −2 indicating stunting, underweight, and wasting, respectively). Parents completed structured questionnaires on feeding patterns (including night feeding), frequency of sweet-food consumption, bedtime toothbrushing, use of fluoride toothpaste, annual oral examinations, vitamin D and calcium supplementation, and parental oral-health knowledge. Group comparisons used chi-square and t-tests; multivariable logistic regression identified factors associated with ECC; Spearman correlation assessed associations between caries count and growth Z-scores.ResultsECC prevalence was 58.68% (223/380), and mean dmft was 2.34 ± 2.35, with no significant differences by sex or age group. In adjusted models, higher sweet-food frequency was associated with greater odds of ECC (OR 1.72, 95% CI 1.19–2.49). Protective factors included vitamin D supplementation for ≥2 years (OR 0.40, 95% CI 0.18–0.86), bedtime toothbrushing (OR 0.22, 95% CI 0.13–0.38), use of fluoride toothpaste (OR 0.04, 95% CI 0.01–0.13), annual oral examinations (OR 0.26, 95% CI 0.15–0.44), and qualified parental oral-health knowledge (OR 0.38, 95% CI 0.23–0.65). Children with ECC had higher proportions of stunting, underweight, and wasting than those without ECC. Caries count was inversely correlated with WHZ (r = −0.649, P < 0.001).ConclusionIn this population, ECC was common. Modifiable behaviors and parental knowledge were strongly associated with ECC, and greater caries severity was linked to lower WHZ, suggesting a relationship between ECC and acute nutritional status. Strengthening sugar intake control, bedtime toothbrushing, fluoride use, and routine dental examinations may help prevent ECC and mitigate its potential impact on growth.